MMAR: sistema web para modelagem molecular tridimensional utilizando realidade aumentada - Mazzuco, Alex Eder da Rocha (2017)
The present work is a part of the Stricto Sensu Postgraduate Program in Network Educational Technologies, following the line of research of Development of Network Educational Technologies, and makes available as its final product a web system called Molecular Modeling with Augmented Reality (MMAR), which uses concepts from Augmented Reality (AR) projected and developed to support the learning of 3D molecular structures. Because of the complexity of these structural compositions, the learning about molecules becomes abstruse, being it even worse due to the fact that the interactivity of the softwares available is limited, in most cases, in motion and other customary actions. Additionally, this difficulty may be explained by the fact that most students do not master the knowledge to work with bimolecular systems, affecting their motivation to study this subject as well. In this context, the AR comes as a differentiated technology, offering new visual opportunities for learning and being an innovative strategy to help students reach better educational results. The objective of this research is to analyze possible influences related to interactivity, usability and motivation provided by the MMAR System. It was developed adopting the Interad Methodology (Digital Interactive Interfaces Applied to Education), directed to the project of graphic interfaces for digital educational materials. To evaluate the system, it was used the Goal, Question, Metric Approach (GQM), establishing the bases to carry out this work. The MMAR System was applied to 25 students in a Chemistry class of the Events Technician Course Integrated to High School in Instituto Federal Farroupilha, in the city of São Borja – Brazil. It was considered that the use of AR technology as a support to the teaching of 3D molecular compositions helped the students retain the knowledge while, simultaneously, they had fun in class, providing the learning in a non-conventional way. In addition, it propitiated that the acquired knowledge was useful and relevant, making the learning a playful and pleasurable activity as well as providing a way to enhance the teaching practices. It was evidenced, in this research, that the system presents innumerous resources, but, at the same time, it is simple, objective and easy to use and understand, presenting a more natural way to manipulate the molecular models, by using markers, and making the students more interested in the subject. It is also pointed out that the AR interface, in the context of this application, may be considered innovative and, for presenting such peculiar and attractive characteristics, it motivates students to want more and more to manipulate (and study) a greater number of molecules. The results show the existence of evidences that aspects related to interactivity, usability and motivation, checked by the system, influenced in the increase of the attractiveness, the curiosity, the attention, the enthusiasm and the relevance of the object of study in such a complex subject in Chemistry as it is the 3D composition in molecular structures.